Balansering, simulering och layoutanalys av ett parallellt monteringsflöde till en produktionslinje - Dinc, Dilara; Bengtsson, Emelie (My University, 2025)
This study examines how a separate door assembly line can be designed and balanced within an existing production environment at Volvo Trucks in Tuve. The aim is to develop a concept proposal that explores possible solutions for an alternative door line, based on production data, line balancing analysis, and simulations. To address questions regarding placement area, assembly sequence, capacity, and how production is affected by disruptions, both a simulation program and a balancing tool have been used. The study takes into account existing logistics, tasks related to door assembly, and space limitations within the factory. Data was collected and used to develop a line balancing proposal for a potential door line. A simulation model, consisting of stations and buffers, was built and analyzed. The study also includes a comparison between two possible areas for placing the door line, considering the factory's layout, flow, and logistical conditions. The result provides a decision-making basis including a balancing proposal for seven assembly stations and a simulation model that can be used as a tool to test production changes and carry out scenario analyses, for example when varying takt times or dealing with disturbances. The goal has been to design an efficient and compact door line concept that can interact smoothly with the existing production line